Effective Industrialization Strategy Analysis in Accelerating Economic Growth in an Archipelago Area: Study in North Maluku Province - Husen, Amran; Runtunuwu, Prince Charles Heston; Hasnin, Muhammad (Society, 2022)
Investigating structural relations between sectors is important from a policy point of view. A clear perspective on cross-sectoral relations can be useful in formulating profitable and appropriate development strategies. This study compares Agricultural Demand Led Industrialization (ADLI) and Export-Led Industrialization (ELI) strategies. In making a comparison, the two strategies are used; multiplier matrix that describes the impact on endogenous variables due to changes in exogenous variables. Impact analysis with a simulation of the investment amount to see the impact on the formation of output, creation of gross value added, absorption of labor, income, and taxes. Cluster analysis aims to classify objects based on the characteristics of the observed object. The One Way Anova test is useful to determine whether there are differences in the investment simulation of each category, ADLI and ELI. The results of this study indicate that the sectors in the ADLI category have advantages in creating gross added value. In contrast, the sectors in the ELI category have advantages in creating output, income, taxes and employment. Furthermore, using the One-Way ANOVA test, it can be concluded that statistically, there is no average difference between ADLI and ELI in the output, labor, income, and tax variables.